Ocean wave observation by multiple drifting buoys in Beaufort Sea of the Arctic Ocean - Katsuno, Tomotaka; Kodaira, Tsubasa; Nose, Takehiko; Uchiyama, Ryosuke; Waseda, Takuji (2022)
The 13th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic research, Thu. 17 Nov. conference object